Subacute presentation of spontaneous diaphragmal rupture: case report - Dejan Hermann; Matevž Srpčič; Marko Bitenc (Zdravniški Vestnik, 2005)
Background: Diaphragmatic injuries are relatively rare and present with non specific symptoms and signs. Late discoveries are almost a rule in all but the most evident cases. Many patients are observed or even treated for suspected other conditions, most often musculosceletal disorders. Patients and methods: We report a case of a 14-year-old boy who presented with left lumbar pain and developed peritonitis six days after strenuous training. A chest X-ray revealed abdominal viscera in the left hemithorax. A large posterolateral rupture of the left diaphragm was found at laparotomy together with herniation of the stomach, spleen and colon. The stomach was perforated and partialy necrotic. Afer partial gastrectomy, repositioning and diaphragmal repair the patient recovered well. Conclusions: If pain in toracoabdominal region is a predominant sign after trauma or endogenous strain, one should consider the posibility of ruptured diaphragm and make a chest X-ray. Operation of diaphragmal hernia is necessary and garanties good results when treated on time.